Las últimas intervenciones arqueológicas en las iglesias de Sant Pere de Terrassa (1995). Aportaciones preliminares sobre la sede episcopal de Egara - Moro, Antonio; Rigo, Antoni; Tuset, Francesc (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 1997)
Abstract Until the end of the sixties, the ancient cathedral ofEgara, composed by two parallel churches (Saint Peter and Saint Mary) and a presumed baptistery (Saint Michael), was presented as a typical Visigothic episcopal group, rebuilt in Romanesque times, having replaced a Late Antique church, according to a mistaken chronology made by Puig i Cadafalch. Although scholars tried many times to correct this chronology, only a reexamination of the stonework and the records of prior excavations (Terme, 1987) taken together with the results of a conference in 1991 (reviewed in Ant. Tard. 2) allowed us to abandon it definitely. Until now, however, we knew nothing about the pre- Romanesque church. A new campaign of archaeological research, conducted by F. Tusset from the University of Barcelona, began in 1995. Possible links between the churches of Saint Michael and Saint Mary in their original state have been dicovered in trenches between the two churches. The question to be asked is whether the complex group dates as early as the fifth century. North of the actual apse of Saint Mary's, part of a lateral apse has been discovered, proving the existence of a church with three aisles and maybe three apses before the Romanesque church was built. The excavation is still in progress.